Congenital dilatation of segmentary intrahepatic biliary ducts: (Caroli disease) associated with lithiasis. Based on an observation. - Schneeberger, Federico; Rabellino, Joaquín; Gutenmajer, Marcos; Falconi, Luis; Boschi, Jorge (Cirugía del Uruguay, 1985)
Based on observation of congenital dilatation of segmentary intrahepatic biliary ducts (Caroli disease) associated with intrahepatic lithiasis, in a patient seeking assistance for severe angiocholangitis that receded with externa! biliary drainage, a brief description is made of this affection, its variations, pathological anatomy and clinicál condition. Hepatic resection being recommended as a radical treatment for localized forms and biliary-digestive derivation, as pallation, in the diffused forms of the disease.